High-mass star formation in Orion possibly triggered by cloud–cloud collision. III. NGC 2068 and NGC 2071. (18th March 2020) - Fujita, Shinji; Tsutsumi, Daichi; Ohama, Akio; Habe, Asao; Sakre, Nirmit; Okawa, Kazuki; Kohno, Mikito; Hattori, Yusuke; Nishimura, Atsushi; Torii, Kazufumi; Sano, Hidetoshi; Tachihara, Kengo; et al.
Abstract: Using the NANTEN2 Observatory, we carried out a molecular-line study of high-mass star forming regions with reflection nebulae, NGC 2068 and NGC 2071, in Orion in the $^{13}$ CO($J = 2$ –1) transition. The $^{13}$ CO distribution shows that there are two velocity components at ${9.0}$ and ${10.5}\:$ km$\:$ s$^{-1}$ . The blue-shifted component is in the northeast associated with NGC 2071, whereas the red-shifted component is in the southwest associated with NGC 2068. The total intensity distribution of the two clouds shows a gap of $\sim\!\! 1\:$ pc, suggesting that they are detached at present. A detailed spatial comparison indicates that the two show complementary distributions. The blue-shifted component lies toward an intensity depression to the northwest of the red-shifted component, where we find that a displacement of ${0.8}\:$ pc makes the two clouds fit well with each other. Furthermore, a new simulation of non-frontal collisions shows that observations from $60^°$ off the collisional axis agreed well with the velocity structure in this region. On the basis of these results, we hypothesize that the two components collided with each other at a projected relative velocity of ${3.0}\:$ km$\:$ s$^{-1}$ . The timescale of the collision is estimated to be ${0.3}\:$ Myr for an assumed axis of the relative motion $60^°$ off the line of sight. We assume that the two most massive early B-type stars in the cloud, illuminating stars of the two reflection nebulae, were formed by collisional triggering at the interfaces between the two clouds. Given the other young high-mass star-forming regions, namely, M 42, M 43, and NGC 2024 (Fukui et al. 2018 a, ApJ, 859, 166; Ohama et al. 2017, arXiv: 1706.05652), it seems possible that collisional triggering has been independently working to form O-type and early B-type stars in Orion in the last Myr over a projected distance of ∼80 pc.